The impact of online social support on psychological resilience and suicidal ideation among sports specialty students under academic-training dual stress: a gender-specific analysis - Hongyi Zhang; Yansong Wang (Frontiers in Psychology)
BackgroundSports specialty students in China face unique “dual stress” from academic demands and athletic training, intensified by cultural values and societal expectations. This stress contributes to elevated suicidal ideation, with limited understanding of how online social support (OSS) and psychological resilience mediate these relationships, particularly across genders.ObjectiveTo investigate the tripartite relationship among academic-training dual stress, OSS, and suicidal ideation, with psychological resilience as a mediator, and to analyze gender-specific differences.MethodsA sample of 1,460 sports specialty students (60% male, 40% female) completed surveys assessing stress, resilience, OSS, and suicidal ideation. Structural equation modeling (SEM) and gender-stratified regression analyses tested mediation and moderation effects.ResultsDual stress positively predicted suicidal ideation, partially mediated by reduced psychological resilience (β = −0.220*** for males, β = −0.180*** for females). OSS buffered this relationship, with stronger moderating effects for females via emotional support (β = −0.330***) and males via instrumental support (β = −0.370***). Gender differences emerged in stress exposure, resilience levels, and OSS preferences.ConclusionPsychological resilience and OSS play critical roles in mitigating the impact of dual stress on suicidal ideation, with gender-specific patterns. Tailored digital interventions leveraging OSS could enhance resilience and reduce suicide risk in this vulnerable group.